TH2.6 Evaulation of the prognostic utility for hENT 1 transmembranous protein in resected hilar cholangiocarcinoma patients. (9th August 2022) - Bird, Nicholas; Manu, Nichola; Shehata, Zak; Fenwick, Stephen; Jones, Robert; Malik, Hassan
Abstract: Aims: Human equilibriative nucleoside transporter protein 1 (hENT1) facilitates nucleoside transport into the cell. Immunohistochemically-detected hENT1 is increased in cholangiocarcinoma tumour cells and in highly metabolising cells. The Mackey 10D7G2 hybridoma has demonstrated prognostic utility in Pancreatic Ductal Adenocarcinoma. The Proteintech Polyclonal hENT1 antibody's prognostic utility has not been assessed. Cellular Ki67 expression is linked to tumour proliferation. This study aims to assess the antibodies' prognostic utility for resectable hilar cholangiocarcinoma. Methods: Between 2009–2016, 54 patients underwent resection for peri-hilar cholangiocarcinoma. Formalin-Fixed Paraffin Embedded blocks from 44 specimens were retrieved. A Tissue-Matched Array was constructed and stained for each antibody. H-scores were utilised to determine expression intensity. Correlation of expression was determined by Pearson correlation co-efficient and Chi-squared. Silencing RNA for transfected HepG2 cell-lines was used to determine accurate hENT1 staining by the Proteintech antibody. Demographic and survival characteristics were acquired from a prospectively held database, and were calculated with global log-rank calculations. Results: There was significant correlation between the Mackey and Proteintech antibodies (p<0.001), and between the Proteintech antibody and Ki67 expression (p= 0.02). Knockdown of hENT1 with silencing RNA transfected HepG2 cells was confirmed by Western blot. The antibodies (Mackey; Proteintech; Ki67) showed no significance for predicting OS (p= 0.75; 0.63; 0.22 respectively). Nodal stage (p= 0.03) and tumour differentiation (p= 0.02) showed prognostic utility. Conclusion: While the Proteintech antibody demonstrates concordance with the 10D7G2 antibody in determining hENT1 expression, they didn't demonstrate significant prognostic ability. Standard histopathological co-variates retain prognostic utility within the cohort.